Retaining Hope While Respecting Patients’ Presumed Wishes: How Substituted Judgement Can Help - Hardy, Natalie; Nortje, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
It is not uncommon for families to wait in hopes of receiving test results that show a treatable mutation, such as in the case of lung cancer. Waiting for such test results can distract families from focusing on a patient’s current pain and suffering, especially when families experience heightened emotions and anticipatory grief. The substituted judgement standard can be helpful in resolving ethical dilemmas by encouraging families to think about what decision a patient would have made if competent, thus preventing unnecessary pain and suffering. This case study sheds light on how the substituted judgement standard was used with a patient’s family and how the family’s hope for a treatable mutation affected their perception of the patient’s clinical condition.